2017
DOI: 10.1186/s13098-017-0297-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of long-term treatment with SGLT2 inhibitors: real-world evidence from a specialized diabetes center

Abstract: BackgroundDiabetes is a progressive disease needing multiple drugs for achieving and maintaining good glycemic control. Sodium-glucose co-transporter 2 inhibitors (SGLT2i) is a novel class of anti-diabetic agent which offers several beneficial effects. However, the long-term effectiveness in clinical practice and safety data of SGLT2 inhibitors is limited, especially in Asian patients. To better understand the effectiveness of SGLT2i in clinical practice, we conducted a retrospective evaluation of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
1
13
2
5
Order By: Relevance
“…However, our study found fewer differences in body weight changes (− 0.5 kg) in real-world comparisons of SGLT2 inhibitors vs. DPP4 inhibitors. Potentially, the reason may be the complicated disease status and comedications in real-world patients, which may affect the ability to achieve optimal weight reduction from SGLT2 inhibitors [31,32]. Given our observations, the effects of SGLT2 inhibitors and DPP4 inhibitors on weight should be considered when individualizing type 2 diabetes therapy.…”
Section: Body Weight Reductionsmentioning
confidence: 92%
“…However, our study found fewer differences in body weight changes (− 0.5 kg) in real-world comparisons of SGLT2 inhibitors vs. DPP4 inhibitors. Potentially, the reason may be the complicated disease status and comedications in real-world patients, which may affect the ability to achieve optimal weight reduction from SGLT2 inhibitors [31,32]. Given our observations, the effects of SGLT2 inhibitors and DPP4 inhibitors on weight should be considered when individualizing type 2 diabetes therapy.…”
Section: Body Weight Reductionsmentioning
confidence: 92%
“…the result of a caloric deficit caused by the elimination of glucose and higher renal water excretion (osmotic diuresis). SGLT-2 inhibitors reduced body weight by as much as 4.7 kg [3][4]. Body weight reduction using SGLT-2 inhibitors gradually slows down and becomes stable after 26-34 weeks [5].…”
Section: Clinical Vignettementioning
confidence: 99%
“…6 It has been shown that therapy with SGLT2 inhibitors results in a loss of 320-400 kcal/d, with an average weight loss of 3.6 to 4.5 kg in 1 to 2 years. 7,8 Diuresis with therapy averages about 300 cm 3 /d, with a slightly higher amount in the first 24 hours of initiating therapy. 9 Currently, over 50 SGLT2 mutations have been identified, resulting in as much as 150 g/1.73/m 2 /d in loss of urinary glucose.…”
Section: Translational Biology and Diabetologymentioning
confidence: 99%
“…SGLT2 inhibitors (‐gliflozins) act by inhibiting renal tubular reabsorption of glucose by inhibition of the SGLT2 protein, which decreases blood glucose, decreases blood pressure, increases water and sodium excretion, and promotes urinary loss of calories in the form of glucose . It has been shown that therapy with SGLT2 inhibitors results in a loss of 320‐400 kcal/d, with an average weight loss of 3.6 to 4.5 kg in 1 to 2 years . Diuresis with therapy averages about 300 cm 3 /d, with a slightly higher amount in the first 24 hours of initiating therapy .…”
Section: Introductionmentioning
confidence: 99%